2011
DOI: 10.1083/jcb.201102031
|View full text |Cite
|
Sign up to set email alerts
|

Persistent activation of Nrf2 through p62 in hepatocellular carcinoma cells

Abstract: Impaired autophagy stabilizes p62 and promotes tumorigenesis through activation of the Nrf2 transcription factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
471
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 522 publications
(495 citation statements)
references
References 49 publications
23
471
1
Order By: Relevance
“…p62 also acts as a cargo receptor for autophagic degradation of ubiquitinated targets (Dikic et al 2010). The results of recent studies revealed that p62 contributes to the accumulation of NRF2 by disrupting the association between NRF2 and KEAP1, which is a negative regulator of NRF2 (Komatsu et al 2010), and that the pathway controlled by NRF2 is activated in p62-positive cases of hepatocellular carcinoma (Inami et al 2011). Therefore, p62 is considered to play an important role in NRF2 stabilization in breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p62 also acts as a cargo receptor for autophagic degradation of ubiquitinated targets (Dikic et al 2010). The results of recent studies revealed that p62 contributes to the accumulation of NRF2 by disrupting the association between NRF2 and KEAP1, which is a negative regulator of NRF2 (Komatsu et al 2010), and that the pathway controlled by NRF2 is activated in p62-positive cases of hepatocellular carcinoma (Inami et al 2011). Therefore, p62 is considered to play an important role in NRF2 stabilization in breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent data also indicate that p62/SQSTM1 plays an important role in the accumulation of NRF2 in carcinoma cells (Komatsu et al 2010, Inami et al 2011). An association between NRF2 accumulation and adverse clinical outcome of patients has been reported in lung (Solis et al 2010, Inoue et al 2012, gallbladder (Wang et al 2010), and ovarian (Konstantinopoulos et al 2011) carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, we propose a role for SQSTM1 in LTC oncogenesis. SQSTM1 accumulation in aggregates is commonly observed in human tumors such as hepatocellular carcinoma and malignant glioma (104)(105)(106)(107). Furthermore, the Ser-351 phosphorylation of SQSTM1 was found to have a crucial role in this Nrf2 activation and the growth of tumor cells (9).…”
Section: Fig 11mentioning
confidence: 99%
“…[6][7][8] In cancer, autophagy is thought to act as a tumor suppressor mechanism during tumor initiation by contributing to the maintenance of genomic integrity and the elimination of procarcinogens. [9][10][11] Accordingly, genetic alterations on autophagic genes, such as BECN1 and ATG7, have been associated with a higher tumor incidence and resistance to therapies; 9,12,13 several tumor suppressor genes also induce autophagy, such as PTEN, TSC1/2, and STK11/LKB1. 14 However, in established solid tumors, autophagy may contribute to tumor adaptation and survival during metabolic stress in addition to favoring cell resistance to therapy.…”
Section: Introductionmentioning
confidence: 99%